A new genus and species of larval Erythraeinae (Acari: Prostigmata: Erythraeidae) from Ukraine and the taxonomic state of Zhangiella - Saboori, Alireza; Khaustov, Alexandr A.; Hakimitabar, Masoud; Hajiqanbar, Hamidreza (Zootaxa, 2009)
Makolia crimeaensis Saboori, Khaustov & Hakimitabar gen. et sp. nov. (Acari: Erythraeidae) is described and illustrated from larvae ectoparasitic on Lasius sp. (Hymenoptera: Formicidae) from Ukraine. A key to world genera of Erythraeinae (larva) is presented and the genus Zhangiella Saboori, Cobanoglu & Bayram is synonymised with Curteria Southcott.